Characterization of a plant-derived monoclonal antibody targeting extracellular enveloped virions of Monkeypox virus - Melendez, Jennifer A.; Sun, Haiyan; Bonner, James; Chen, Qiang (Frontiers in Plant Science, 2024)
In 2022, the global outbreak of monkeypox virus (MPXV) with increased human-to-human transmission triggered urgent public health interventions. Plant-derived monoclonal antibodies (mAbs) are being explored as potential therapeutic strategies due to their diverse mechanisms of antiviral activity. MPXV produces two key infectious particles: the mature virion (MV) and the extracellular enveloped virion (EV), both essential for infection and spread. Effective therapies must target both to halt replication and transmission. Our prior research demonstrated the development of a potent neutralizing mAb against MPXV MV. This study focuses on developing a plant-derived mAb targeting MPXV EV, which is critical for viral dissemination within the host and generally resistant to antibody neutralization. Our findings reveal that the mAb (H2) can be robustly produced in Nicotiana benthamiana plants via transient expression. The plant-made H2 mAb effectively targets MPXV EV by binding specifically to the A35 MPXV antigen. Importantly, H2 mAb shows notable neutralizing activity against the infectious MPXV EV particle. This investigation is the first to report the development of a plant-derived anti-EV mAb for MPXV prevention and treatment, as well as the first demonstration of anti-MPXV EV activity by an mAb across any production platform. It highlights the potential of plant-produced mAbs as therapeutics for emerging infectious diseases, including the MPXV outbreak.